ExiFRET: Flexible tool for understanding FRET in complex geometries - Deplazes, Evelyne; Jayatilaka, D.; Corry, B. (SPIE, 2012)
Fluorescence resonance energy transfer (FRET) can be utilized to gain low-resolution structural information by reporting on the proximity of molecules or measuring inter- and intramolecular distances. This method exploits the fact that the probability of the energy transfer is related to the separation between the fluorescent molecules. This relationship is well described for a single pair of fluorophores but is complicated in systems containing more than two fluorophores. Here, we present a Monte Carlo calculation scheme that has been implemented through a user-friendly web-based program called ExiFRET that can be used to determine the FRET efficiency in a wide range of fluorophore arrangements. ExiFRET is useful to model FRET for individual fluorophores randomly distributed in two or three dimensions, fluorophores linked in pairs or arranged in regular geometries with or without predefined stoichiometries. ExiFRET can model both uniform distributions and fluorophores that are aggregated in clusters. We demonstrate how this tool can be employed to understand the effect of labeling efficiency on FRET efficiency, estimate relative contributions of inter- and intramolecular FRET, investigate the structure of multimeric proteins, stoichiometries, and oligomers, and to aid experiments studying the aggregation of lipids and proteins in membrane environments. We also present an extension that can be used to study instances in which fluorophores have constrained orientations.